IMPROVING THE QUALITY OF LEARNING MATHEMATICS THROUGH INNOVATIVE LEARNING MEDIA - Sigit Dwi Laksana (Universitas Pendidikan Ganesha, 2017)
As a hope for an educator so that children can become children of his protégé. An educator is the most important part of which is inseparable from the process of learning. The results of the learning process depend very much on the role of teacher, teacher/educator designing, executing and evaluating. In order to make the learning process can be run with a maximum of and in accordance with the goal of educators so teachers can use the learning tool, in this case, is the medium of instruction. Lots of media types there are learning at school, of which simple or complicated. But many teachers who are encountering less innovative and creative in terms of learning media, and produced illustrations for designing learning media is very important and necessary by the teacher since by doing development as well as innovate can improve student learning and desire a great fit with the needs of the students. Therefore researchers interested and doing research on quality improvement of learning with innovative learning media. This research aims to develop the creative power of teachers to continue to create media innovative and creative learning.